If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = 6 + y Add '-6' to each side of the equation. 6 + -6 = 6 + -6 + y Combine like terms: 6 + -6 = 0 0 = 6 + -6 + y Combine like terms: 6 + -6 = 0 0 = 0 + y 0 = y Solving 0 = y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 0 + -1y = y + -1y Remove the zero: -1y = y + -1y Combine like terms: y + -1y = 0 -1y = 0 Divide each side by '-1'. y = 0 Simplifying y = 0
| 5(-3+7x)=-330 | | x+x*0.09=1000 | | 2(0.3r+1)=24 | | x-1/3=4/3 | | 5x+1=43-2x | | 2x^2+5x+6=x^2 | | 21x-16y=120 | | 10x-42+17x=13+14 | | .0855t^2-.916t+1.737=0 | | 8+2t-2=7t+8-4t | | 3(X+2)(X+2)+16(X+2)+5= | | 3+(5x-6/4) | | 3mx-9y=2(m+2b) | | x-7=144 | | 4s^2+16s-as-4a= | | 2/3(3/5) | | (5/6)t+4=(1/6)t-2 | | 13x+3x-5=27 | | .0825t^2-.886t+1.752=0 | | 5x-15=x+25 | | -x^2+11=0 | | -8+x/8=-12 | | 6(6x+5)=-390 | | (10)+c^3/3=c^3/(3)+10 | | 6x+3=4x+7 | | 3x^2+5x+343=0 | | 11x-2(4x-6)=18 | | 2-20q-3q+12=5+4q+15 | | 2x+40=6x+8 | | 3q+6+2q+3=13q+19-3q | | 3k=7k+12 | | (2x+40)+(6x+8)=180 |